CHANGES IN THE LEVEL OF TROPHOBLASTIC ß-GLYCOPROTEIN IN IVF PREGNANCIES COMPLICATED BY MISCARRIAGE (KIUT Publication, 2025)
This study evaluated the level of trophoblastic ß-glycoprotein (TBG) in 143 pregnant women who conceived via in vitro fertilization (IVF) and experienced miscarriage. A significant decrease in TBG levels was identified as the most critical risk factor: when TBG levels dropped fivefold or more, the probability of spontaneous pregnancy loss reached 100%. When TBG levels decreased by 2–4 times, the risk of miscarriage was 30–33%. The level of trophoblastic ß-glycoprotein (TBG) was assessed in the development of miscarriage in 143 pregnant women with IVF. The most dangerous is a sharp decrease in the level of TBG: if the indicators have decreased by 5 times or more, the probability of spontaneous termination of pregnancy is 100%. If the TBG indicator is reduced by 2-4 times, the probability of interruption is 30-33%.